Structural Comparisons of Ligand-gated Ion Channels in Open, Closed, and Desensitized States Identify a Novel Propofol-binding Site on Mammalian γ-Aminobutyric Acid Type A Receptors. (April 2015) - Franks, Nicholas P.
<x xml:space="preserve">Abstract</x> Background: Most anesthetics, particularly intravenous agents such as propofol and etomidate, enhance the actions of the neurotransmitter γ-aminobutyric acid (GABA) at the GABA type A receptor. However, there is no agreement as where anesthetics bind to the receptor. A novel approach would be to identify regions on the receptor that are state-dependent, which would account for the ability of anesthetics to affect channel opening by binding differentially to the open and closed states. Methods: The open and closed structures of the GABA type A receptor homologues Gloeobacter ligand–gated ion channel and glutamate-gated chloride channel were compared, and regions in the channels that move on channel opening and closing were identified. Docking calculations were performed to investigate possible binding of propofol to the GABA type A β3 homomer in this region. Results: A comparison between the open and closed states of the Gloeobacter ligand–gated ion channel and glutamate-gated chloride channel channels identified a region at the top of transmembrane domains 2 and 3 that shows maximum movement when the channels transition between the open and closed states. Docking of propofol into the GABA type A β3 homomer identified two putative binding cavities in this same region, one with a high affinity and one with a lower affinity. Both cavities were adjacent to a histidine residue that has been photolabeled by a propofol analog, and both sites would be disrupted on channel closing. Conclusions: These calculations support the conclusion of a recent photolabeling study that propofol acts at a site at the interface between the extracellular and transmembrane domains, close to the top of transmembrane domain 2.